2015
DOI: 10.1002/bies.201500026
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of the mammalian circadian timing system: Light can control peripheral clocks independently of the SCN clock

Abstract: A vast network of cellular circadian clocks regulates 24‐hour rhythms of behavior and physiology in mammals. Complex environments are characterized by multiple, and often conflicting time signals demanding flexible mechanisms of adaptation of endogenous rhythms to external time. Traditionally this process of circadian entrainment has been conceptualized in a hierarchical scheme with a light‐reset master pacemaker residing in the hypothalamus that subsequently aligns subordinate peripheral clocks with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 76 publications
2
66
0
2
Order By: Relevance
“…Light masking of locomotor activity was, however, absent in the mutant mice as disclosed in animals under short ultradian light cycles in line with previous findings that suppression of activity by light is primarily dependent upon ipRGC signaling [25]. It has been suggested that in addition to the classical retinohypothalamic pathway that directly entrains the SCN clock, a secondary neural pathway bypassing the SCN clock could relay photic signals for synchronization of peripheral clocks [11]. Our results implicate ipRGCs as the sole source of photic signals to peripheral clock synchronization either via the classical retinohypothalamic pathway or the putative SCN clock bypassing pathway…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Light masking of locomotor activity was, however, absent in the mutant mice as disclosed in animals under short ultradian light cycles in line with previous findings that suppression of activity by light is primarily dependent upon ipRGC signaling [25]. It has been suggested that in addition to the classical retinohypothalamic pathway that directly entrains the SCN clock, a secondary neural pathway bypassing the SCN clock could relay photic signals for synchronization of peripheral clocks [11]. Our results implicate ipRGCs as the sole source of photic signals to peripheral clock synchronization either via the classical retinohypothalamic pathway or the putative SCN clock bypassing pathway…”
Section: Discussionsupporting
confidence: 84%
“…In these mice, peripheral oscillators are able to sustain circadian rhythmicity that are phase-locked with external LD cycles, even in the absence of a functional central SCN oscillator [3739]. These results suggest that a functional SCN clock is not required for entrainment of peripheral clocks and that light can directly entrain peripheral tissues via brain clocks other than the SCN [11, 39]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, light is the major Zeitgeber (German for 'time giver'). A master pacemaker located in the hypothalamic suprachiasmatic nucleus (SCN) acts as the major interface between endogenous rhythms and environmental time cues such as the light-darkness cycle (Husse et al 2015). The SCN receives photic input from intrinsically photoreceptive retinal ganglion cells (ipRGCs) expressing the photopigment melanopsin to entrain SCN clock gene expression and neuronal activity (Hankins et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional view of the relationship between the SCN and the peripheral cellular clocks is believed to be hierarchal in nature, with the central clock of the SCN regulating the timing of peripheral clocks; however, recent research is beginning to show that the relationship may be more "federated," such that various oscillators are equal to one another (Husse, Eichele, & Oster, 2015, p. 1120. Therefore, it is likely that peripheral clocks are influenced by independent zeitgebers (e.g., light-dark cycles, hormones, bloodborne signals, body temperature; Husse et al, 2015).…”
Section: Circadian Rhythmsmentioning
confidence: 99%